Letter: bias in clinical trials of the symptomatic effects of the low FODMAP diet for irritable bowel syndrome—getting the facts right. Authors' reply. Issue 3 (4th July 2017) - Krogsgaard, L. R.; Lyngesen, M.; Bytzer, P.
Abstract : Linked Content This article is linked to Krogsgaard et al, and Gibson et al papers. To view these articles visithttps://doi.org/10.1111/apt.14065 andhttps://doi.org/10.1111/apt.14150 .